(3TQM ddTeSjIs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B... (3bGd GdebGdI GdKGfjI aj GdbVGjG hCMcGegG hajgG ebOeI hKdGKI aUhd CeG GdebOeI aaj JYQja GbVjI hCbSGegG GdChdjI (B, (3GdbVjI bhd jUM Cf jbGd dbGFdg Cfg UGOb Ch cGPH Cbhd deG aQZJ ef eHGMK Gdbhds
(3BNQgG (B:s
... (3GeG ehVhYGJ GdYde Ch LRFjGJgG Ch CYQGVgG GdPGJjI Ch LRFjGJgG hGeG eMehdGJgG agj GdCYGQV GdPGJjI dehVhY GdYde adGHO Gf jchf NGQLI Yf ehVhYGJgG dGeJfGY Gf jchf LRA GdTjA eWdhHG HGdHQgGf (B...s
(3JHUQI GdYfhGf (B:s
(3bO jchf TQM GdbWH GdQGRj GdeSei JMQjQ GdbhGYO GdefWbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdadSaI hGdefWbs